Paraplegia 2021
DOI: 10.5772/intechopen.94920
|View full text |Cite
|
Sign up to set email alerts
|

Use of Exoskeletons in the Treatment and Rehabilitation of Paraplegia Patients

Abstract: This chapter presents a review that includes five robotic exoskeletons used in the rehabilitation of paraplegic patients, highlighting the qualities of each one and offering the doctor and the rehabilitator a tool to select the exoskeleton that is most appropriate to the needs of their patient and a more satisfying and integral therapy. A systematic search was carried out in different platforms of scientific interest, the publications that met the inclusion criteria were selected. The information collected was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…8 However, the exoskeletons are prohibitively costly (65 000-100 000 $) and may not be available universally. 9 However, many RCTs and Cochrane meta-analysis have shown that robotic exoskeletons have not yielded robust advantages. 10,11 However, the disappointing results with conservative treatment led to search for operative procedures.…”
Section: Discussionmentioning
confidence: 99%
“…8 However, the exoskeletons are prohibitively costly (65 000-100 000 $) and may not be available universally. 9 However, many RCTs and Cochrane meta-analysis have shown that robotic exoskeletons have not yielded robust advantages. 10,11 However, the disappointing results with conservative treatment led to search for operative procedures.…”
Section: Discussionmentioning
confidence: 99%